2015
DOI: 10.1016/j.ccell.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Combined MYC and P53 Defects Emerge at Medulloblastoma Relapse and Define Rapidly Progressive, Therapeutically Targetable Disease

Abstract: SummaryWe undertook a comprehensive clinical and biological investigation of serial medulloblastoma biopsies obtained at diagnosis and relapse. Combined MYC family amplifications and P53 pathway defects commonly emerged at relapse, and all patients in this group died of rapidly progressive disease postrelapse. To study this interaction, we investigated a transgenic model of MYCN-driven medulloblastoma and found spontaneous development of Trp53 inactivating mutations. Abrogation of p53 function in this model pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
198
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(221 citation statements)
references
References 46 publications
8
198
0
1
Order By: Relevance
“…Furthermore, p53 loss of function gives rise to tumors that can acquire growth and survival mechanisms that are resistant to the reintroduction of functional p53. This is in stark contrast with a medulloblastoma GEM model driven by expression of MYCN and p53 deficiency, GTML/Trp53 KI/KI (GTML; Glt1-tTA/TRE-MYCN-Luc), where restoration of functional p53ER TAM by Tam led to increased survival and inhibition of tumor growth (5). Other transgenic models of p53 loss of function do, however, develop tumors that display partial resistance to the restoration of functional p53ER…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, p53 loss of function gives rise to tumors that can acquire growth and survival mechanisms that are resistant to the reintroduction of functional p53. This is in stark contrast with a medulloblastoma GEM model driven by expression of MYCN and p53 deficiency, GTML/Trp53 KI/KI (GTML; Glt1-tTA/TRE-MYCN-Luc), where restoration of functional p53ER TAM by Tam led to increased survival and inhibition of tumor growth (5). Other transgenic models of p53 loss of function do, however, develop tumors that display partial resistance to the restoration of functional p53ER…”
Section: Discussionmentioning
confidence: 89%
“…Examples of second-site SMOis include the antifungal agent itraconazole and the cyclopamine derivative IPI-926 (saridegib), both of which have shown promise in preclinical studies (65,66). Inhibitors of downstream components of the SHH pathway include arsenic trioxide, which can promote GLI2 degradation (65); bromodomain inhibitors, which not only reduce expression and transcriptional activity of the SHH target MYCN (67) but also impair the function of GLI1 and GLI2 (68); and Aurora kinase A inhibitors, some of which can impair cell cycle progression as well as destabilize MYCN (69)(70)(71). The observation of increased PI3K pathway activity in tumors that develop resistance to SMOis (63,64), along with reports of recurrent mutations affecting this pathway (12,42), has suggested that PI3K inhibition may be an important strategy for preventing or overcoming resistance of SHH-MB.…”
Section: Shh Subgroupmentioning
confidence: 99%
“…Combined MYC and TP53 defects have been found in patients with relapsed MB (70), and thus, these mouse models may represent valuable tools for studying recurrent tumors. Because TP53 aberrations have not been found in newly diagnosed G3-MBs, the search has begun for alternative "second hits" that can cooperate with Myc to drive tumorigenesis in mice.…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Current treatment strategies include a combination of surgery, radiotherapy, and chemotherapy, which have achieved 70%-80% 5-yr survival rates; however, recurrence is common and often proves fatal (Hill et al 2015). In addition, both the brain exposure to ionizing radiation and the systemic exposure to chemotherapy agents can induce severe side effects, leading to mental and physical disability of the affected children.…”
mentioning
confidence: 99%